Number and Linear Attenuation Coefficient Variation in Hypertensive Patients with Brain Hemorrhage and Infarction Using CT Scan - Gnawali, Suresh; Aryal, Sheskant; Shreshta, Ananda Prasad (Journal of Institute of Science and Technology, 2015)
The aim of this paper is to study the variation of brain matter of Nepalese patients using CT scan. CT number and linear attenuation coefficient (LAC) of cortical bone are found largest among other brain matters, indicating the largest density. All brain matters except cortical bone show low association indicating slight changing trend with age. The cortical bone under 10 years shows low value of LAC and CT number, indicating cortical bone towards maturation whereas cortical bone shows no significant increase with age above 10 years. There is no much significant relation by gender in brain hemorrhage and infarction. Journal of Institute of Science and Technology, 2014, 19(2): 129-134